POSSIBILITY OF USE OF MARKETING TECHNOLOGIES IN ATTRACTING SPECIALISTS TO EDUCATIONAL INSTITUTIONS - Tymchyk, Olena (Educological discourse, 2019)
Modern educational institutions require qualified teachers who can provide the educational services of proper level. The problem of providing educational institutions with pedagogical staff has been relevant for a long time, till nowadays. It can be solved by a consecutive marketing program, elements of which can be found on the school websites. The author carried out a general analysis of the websites of Ukrainian schools (both public and private ones) and concluded that there is a solid lack of information, which should be aimed specifically for young graduates. The author believes that during the process of development of marketing program, the governance of schools ought to orientate it not only based on necessities of consumers of educational services, but also made it suitable for teachers who in future can apply for work in these institutions. According to the author, the pages of websites devoted to the personnel policy of schools should also contain the requirements to the possible candidates for vacant places in these institutions. It is also important to place the information about working conditions - material and technical support of the educational institution. This will allow young specialists to make conclusions about the possibility of realizing their knowledge and practical skills. The author believes that young specialists are interested in the information concerning the projects in which an educational institution is involved. Such information indicates the level of development of the institution and possible perspectives for its employees. The author suggests the use of the "reverse" orientation of the marketing activities of the school regarding employees, which will encourage its attractiveness for young professionals, and will also help the educational sphere in its competition for highly skilled workers.